A new approach for breeding low‐temperature‐resistant Volvariella volvacea strains: Genome shuffling in edible fungi. (September 2016) - Zhu, Ziping; Wu, Xiao; Lv, Beibei; Wu, Guogan; Wang, Jinbin; Jiang, Wei; Li, Peng; He, Jianhua; Chen, Jianzhong; Chen, Mingjie; Bao, Dapeng; Zhang, Jinsong; et al.
Abstract: Volvariella volvacea is difficult to store fresh because of the lack of low‐temperature resistance. Many traditional mutagenic strategies have been applied in order to select out strains resistant to low temperature, but few commercially efficient strains have been produced. In order to break through the bottleneck of traditional breeding and significantly improve low‐temperature resistance of the edible fungus V. volvacea, strains resistant to low temperature were constructed by genome shuffling. The optimum conditions of V. volvacea strain mutation, protoplast regeneration, and fusion were determined. After protoplasts were treated with 1% (v/v) ethylmethylsulfonate (EMS), 40 Sec of ultraviolet (UV) irradiation, 600 Gy electron beam implantation, and 750 Gy 60 Co‐γ irradiation, separately, the lethality was within 70%–80%, which favored generating protoplasts being used in following forward mutation. Under these conditions, 16 strains of V. volvacea mutated by EMS, electron beam, UV irradiation, and 60 Co‐γ irradiation were obtained. The 16 mutated protoplasts were selected to serve as the shuffling pool based on their excellent low‐temperature resistance. After four rounds of genome shuffling and low‐temperature resistance testing, three strains (VF1, VF2, and VF3 ) with high genetic stability were screened. VF1, VF2, and VF3 significantly enhanced fruit body shelf life to 20, 28, and 28 H at 10 °C, respectively, which exceeded 25%, 75%, and 75%, respectively, compared with the storage time of V23, the most low‐temperature‐resistant strain. Genome shuffling greatly improved the low‐temperature resistance of V. volvacea, and shortened the course of screening required to generate desirable strains. To our knowledge, this is the first paper to apply genome shuffling to breeding new varieties of mushroom, and offers a new approach for breeding edible fungi with optimized phenotype.